ADC Topology Based on Compressed Sensing for Low Power Brain Monitoring. (2015) - Lange, Heiner; Schmale, Sebastian; Knoop, Benjamin; Peters-Drolshagen, Dagmar; Paul, Steffen
Abstract: This paper presents a new analog-to-digital converter (ADC) topology for continuous brain monitoring, which achieves low power operation by using compressed sensing (CS) for sub-Nyquist data acquisition, reducing the number of required amplifiers compared to other implementations. The topology is validated by simulations with real-world measured neurological data.